Differential Requirement of Vav Proteins for Btk-dependent and –Independent Signaling During B Cell Development - Betzler, Annika C.; Kieser, Sebastian; Fiedler, Katja; Laban, Simon; Theodoraki, Marie-Nicole; Schuler, Patrick J.; Wirth, Thomas; Tedford, Kerry; Fischer, Klaus-Dieter; Hoffmann, Thomas K.; Brunner, Cornelia (Frontiers in Cell and Developmental Biology, 2022)
Btk and Vav proteins are all components of the signalosome that builds upon B cell receptor (BCR) activation. However, the role of Vav proteins within the signalosome is quite complex and not yet fully understood. Until now, studies of these have focused predominantly on a deficiency of Vav proteins alone or in combination with other Vav protein family members. Since a physical association of Btk with Vav was shown previously, we asked whether these molecules lie in the same or independent signaling pathways. By analyzing Vav1 and Vav3 single knock-out mice and generating double-knock-out animals deficient for either Vav1 or Vav3 and Btk, we observed, in line with previous publications, no severe B cell developmental defects when either Vav1 or Vav3 alone are not expressed. However, a simultaneous deficiency of Btk together with either Vav1 or Vav3 leads to a severe reduction of splenic B cells, which exhibit an immature phenotype. B cell developmental defects of Btk/Vav1-double deficient mice in the periphery were more severe than those observed in Btk-single-deficient animals. Additionally, morphological changes in splenic microarchitecture were observed in double- but also in single-knock-out mutants. These observations were accompanied by reduced BCR-induced Ca2+ mobilization, proliferation, germinal center formation and immunoglobulin secretion. Although deletion of Btk alone impaired Ca2+ mobilization upon BCR activation, the defect was even more severe when Vav1 or Vav3 were also mutated, indicating that Btk and the Vav proteins act in separate pathways that converge on Ca2+ signaling. In vitro ASC differentiation suggests that both B and T cells contribute to the observed phenotype of a Btk/Vav-double deficiency. Our results show that Vav proteins and Btk are both components of the BCR-activated signalosome but control separate signaling pathways important for B cell development.